2013
DOI: 10.1007/s12291-013-0382-4
|View full text |Cite
|
Sign up to set email alerts
|

PCT as a Prognostic Marker in Cardiac Patients with Neutropenic Sepsis: Two Case Reports

Abstract: Procalcitonin (PCT) is an innovative and highly specific marker for diagnosis of clinically relevant bacterial infection and sepsis. PCT supports early diagnosis and Clinical decision making. A retrospective study of two classical cases of neutropenic sepsis with elevated PCT levels in cardiac ICU was done. PCT was analyzed using Elecsys Brahms PCT kit. Serum PCT levels \0.5 ng/ml and ANC\1,000/mm 3 was taken as cutoff. The first patient had initial high levels of PCT 100 ng/ml, TLC 13,600/mm 3 and ANC 12,250/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…The concept of PCT clearance for assessing the prognosis of sepsis introduces the dynamic change of PCT that is more meaningful than the absolute value of PCT. [14,16,17] Our study has shown similar results. Analysis of endotoxins showed that median values on day 7 are also significantly different between the two groups as 0.1240 EU/mL (0.0443 EU/mL, 0.2320 EU/ mL) vs. 0.4813 EU/mL (0.2387 EU/mL, 0.7412 EU/mL) (Z=-2.583, P=0.010).…”
Section: Discussionsupporting
confidence: 83%
“…The concept of PCT clearance for assessing the prognosis of sepsis introduces the dynamic change of PCT that is more meaningful than the absolute value of PCT. [14,16,17] Our study has shown similar results. Analysis of endotoxins showed that median values on day 7 are also significantly different between the two groups as 0.1240 EU/mL (0.0443 EU/mL, 0.2320 EU/ mL) vs. 0.4813 EU/mL (0.2387 EU/mL, 0.7412 EU/mL) (Z=-2.583, P=0.010).…”
Section: Discussionsupporting
confidence: 83%
“…PCT, the precursor of calcitonin, is generated at low levels in serum by thyroid C cells under physiological conditions. However, under pathological conditions such as bacterial infections, PCT levels in serum rise significantly 11 , 12 and tissues other than the thyroid, such as the lungs and intestines, mainly produce PCT. PCT levels increase in cerebral infarction 7 , 13 , 14 as well as in severe trauma 19 , 20 , even without bacterial infection 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response is an important factor in ischemic stroke 4 , 5 , and inflammatory markers such as PCT and high-sensitivity C-reactive protein (CRP) can help to determine the severity and prognosis of acute cerebral infarction 6 10 . PCT has been widely used in clinical practice as a diagnostic marker for serious bacterial infections and sepsis, as well as a prognostic marker for patients with infections 11 , 12 . Recent studies have found that PCT is an independent risk factor for cerebral infarction 7 , 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical markers are also being increasingly applied for the early diagnosis and management of sepsis. Ideal biochemical markers are characterized by the following features: they could be easily and widely applied clinically; provide opportunities for intervention and rapid improvement of prognosis; and provide information on prognosis as well as, or better than presently utilized evaluation methods serum levels of PCT [ 14 ], CRP, and Lac [ 15 , 16 ] have been widely used as clinical indicators to evaluate the severity of infectious diseases, and these markers reflect the level of inflammation in the body. While, PCT, CRP, and Lac present in the serum reflect the degree of inflammatory response during sepsis, they are not sufficient to predict the prognosis of sepsis.…”
Section: Discussionmentioning
confidence: 99%